Changes of Ocular Dimensions as a Marker of Disease Progression in a Murine Model of Pigmentary Glaucoma - Fiedorowicz, Michał; Wełniak-Kamińska, Marlena; Świątkiewicz, Maciej; Orzeł, Jarosław; Chorągiewicz, Tomasz; Toro, Mario Damiano; Rejdak, Robert; Bogorodzki, Piotr; Grieb, Paweł (Frontiers in Pharmacology, 2020)
Purpose The elevation of intraocular pressure (IOP), a major risk factor in glaucoma, is an important parameter tracked in experimental models of this disease. However, IOP measurement in laboratory rodents is challenging and may not correlate with some key pathological events that occur in the development of glaucoma. The aims of this study were to quantify changes in ocular morphology in DBA/2J mice that develop spontaneous, age-dependent, pigmentary glaucoma and to check the possible correlation of these parameters with IOP. Method Eye morphology was evaluated with MRI in DBA/2J, DBA/2J-Gpnmb+/SjJ, and C57BL/6J female mice ages 3, 6, 9, 12, and 15 months. The animals were anesthetized with isoflurane. A planar receive-only surface coil (inner diameter = 10 mm) was placed over each animal’s left eye and the image was acquired with a 7T small animal-dedicated magnetic resonance tomograph and T2-weighted TurboRARE sequence. Ocular dimensions were manually quantitated using OsiriX software. IOP was measured with rebound tonometry. Results In the control animals, no age-related changes in the ocular morphology were noted. Since 6 months of age, the anterior chamber deepening and elongation of the eyeballs of DBA/2J mice was detectable. We found a significant, positive correlation between IOP and axial length, anterior chamber area, or anterior chamber width in C57BL/6J mice but not in DBA/2J mice. However, after excluding the measurements performed in the oldest DBA/2J mice (i.e. analyzing only the animals ages 3 to 12 months), we demonstrated a significant positive correlation between IOP and anterior chamber width. Conclusion High-resolution magnetic resonance imaging of the eye area in mice enables reproducible and consistent measures of key dimensions of the eyeball. We observed age-dependent alterations in the eye morphology of DBA/2J mice that mostly affected the anterior chamber. We also demonstrated a correlation between some of the ocular dimensions and the IOP of C57Bl/6J mice and DBA/2J mice with moderately advanced glaucomatous pathology.